Bridging the gap in islamic finance for climate action: A bibliometric analysis - Laela Rizki Fauzia; Ariyanto Adhi Nugroho (Nur Science Institute, 2026)
Climate change is one of the most pressing challenges in contemporary global development, necessitating large-scale, sustained financing for both mitigation and adaptation. In this context, Islamic finance, grounded in the principles of justice, transparency, and sustainability, offers a distinctive normative and operational framework to support climate action. However, the contribution of Islamic finance to climate-related financing remains relatively limited, constrained by structural and operational barriers at both national and global levels, including regulatory fragmentation, limited standardization, and underdeveloped green financial instruments. This study employs bibliometric analysis to map the development of research connecting Islamic finance with global climate action. The data were drawn from 73 peer-reviewed documents retrieved from the Scopus database spanning the period 2000 to early 2026. The analysis identified five major thematic clusters and three distinct phases of research development, namely a scientific and environmental foundation phase (2014–2017), a socio-religious integration phase (2018–2020), and a strategic financial policy phase (2021–present). Academic attention has progressively shifted from environmental pollution measurement toward Islamic financial instruments as climate solutions, yet a significant gap remains in integrating these instruments with technical environmental science literature.